Brain food - Cornish, Richard, 1967- (Melbourne University Press, 2017)
Is pork butt the new pork belly? Whose room temperature are we talking about? And can you freeze cheese? (Yes, but why would you want to?) These are some of the burning questions at the heart of every kitchen. Food science, etiquette, mythbusting, history and common sense-there is no subject too big or too small for Richard Cornish to answer in his weekly Brain Food columns, which have been must-reads for years. Brain Food is a collection of the best cooks' conundrums and their surprising answers.